Digital taxation and tax compliance in Indonesian Marketplaces: A qualitative study of Shopee Sellers - Rodhiyah Rodhiyah; Andi Iswoyo; Antoni Antoni; Pujianto Pujianto (AFRE (Accounting and Financial Review), 2026)
This study examines how Indonesian marketplace sellers interpret and respond to evolving income tax arrangements in e-commerce, focusing on inclusivity and practical compliance in platform-based trade. Previous studies on digital taxation have largely focused on measurable compliance outcomes using quantitative approaches, providing limited understanding of how MSME sellers interpret settlement deductions in marketplace transactions. Using an interpretive qualitative case study approach, semi-structured interviews were conducted with five active Shopee sellers representing different product categories and seller tiers. The findings reveal three main themes. First, sellers experience a perception–regulation gap, as deductions displayed in transaction settlements are often interpreted as taxes, although they may also include platform fees and other charges. This creates uncertainty regarding the nature of the deductions and contributes to perceptions of unfairness. Second, sellers adopt various margin-protection strategies, including price adjustments, product modifications, and the use of paid platform services. Third, sellers’ express expectations for a more transparent and practical system, including clearer invoice labeling, simplified procedures for micro sellers, and integrated guidance within marketplace platforms. This study contributes to the literature by highlighting how transparency, administrative burden, and platform governance shape sellers’ perceptions of digital taxation and tax compliance. As an exploratory qualitative study based on a small sample from a single marketplace, the findings should be interpreted within their context.